Mamin-Sibiryak's literary legacy and prospects of regional literary studies (Филологический класс, 2012)
The article observes the key areas of the research of Mamin Sibiryak’s body of literary works, i.e. literary method and axiology, geopoetics, genre system and the language skill of the outstanding Ural writer. The objects of the contemporary Mamin-Sibiryak studies are linked to the prospects of Ural Region literary studies.